Pertanggungjawaban Pidana Pencemaran Nama Baik Melalui Media Sosial Di Wilayah Kota Kupang - Monika Yuliani Mamir Tanar; Deddy R.C Manafe; Adrianus D. Dima (Lembaga Pengembangan Kinerja Dosen, 2024)
Criminal responsibility is the application of the law to the perpetrator of a criminal offense for an act that is contrary to the applicable rules of law. Social media allows anyone to participate in receiving ideas, comments, and information without the limitations of space and time. This triggers the misuse of social media and the lack of ethics in communicating Good name defamation alone is a crime against a person's honor because it is related to insults that result in defaming another person's name. The method of research is empirical law, Anahsis, the regulation of defamation and insult in this case is based on a single indictment that was united by the panel of judges to the defendant, namely Article 45 paragraph (3) jo Article 27 paragraph (3) of Law Number 19 of 20 16. The punishment for the defendant is based on a single charge, namely imprisonment for 3 (three) months where the criminal elements have been fulfilled.